O Banco na Palma da Mão - A Institucionalização do Uso do Mobile Banking: Estudo em uma Agência Bancária de Guarapuava/Pr - Silva, Jéssica Martins da (2018)
Recognizing the importance of financial institutions for the economy and innovations that have occurred in the banking sector, this study aimed to verify how the use of mobile banking is being institutionalized under the perspective of clients and employees of a bank agency located in the city of Guarapuava / PR. The theoretical and analytical basis is based on the Institutional Theory, especially in the stages of institutionalization as defined by Tolbert and Zucker (1999) - habitualization, objectification and sedimentation; and in studies related to mobile banking. As for the methodology, the first phase of the study was characterized by qualitative research with descriptive purposes, whose data collection occurred through semi-structured interviews with eight employees, journal of research and reports and documents provided by the organization. Now, the second phase presented a quantitative nature, questionnaires with Likert-type scale were applied to a sample of 382 clients. Under the perspective of the employees, the interviewees considered mobile banking an innovation that occurred due to external pressures to the organization; the interviewees also stated that there is no concordance of all involved (clients and employees) regarding the use of mobile banking. However, employees recognize the benefits of using the tool, positive results have already been realized in the day-to-day, and they believe its use will be consolidated. Under the perspective of the costumers, 63.4% of those respondents are users of mobile banking and 36.6% claimed not to use this self-service tool. Non-users are not aware and / or have insecurity about using it. They also considered other factors relating to non-use: incompatibility of application with some mobile phones, complexity regarding the use of technologies, and the need for initial demonstration of the use of the application. By means of the statistical results, three distinct groups were observed among the clients surveyed; thus, the groups were classified as low, moderate and high, relating to the stages of institutionalization. In this context, the stage of sedimentation is more perceived by costumers, however, it cannot be said that the tool is fully institutionalized. The organizational consciousness must be worked on, so that the culture to encourage the use of mobile banking is internalized by its members and passed on to clients; highlight the security and evidence that the user is protected in the event of fraud. In this way, it is considered that, under the perspective of employees and clients, mobile banking has reached the stage of habitualization defined by Tolbert and Zucker (1999): in this stage, causal forces are characterized as a process of innovation, in the studied context it refers to the introduction of the use of mobile banking, incited by factors external to the organization - technological changes and market forces - the fifth wave of banking technological innovation and the use of mobile banking by society. This stage is also characterized by the presence of new structural arrangements, which are transformed into policies, rules or procedures (normative manuals and contracts regarding the use of mobile banking). As a contribution, the present study helped in understanding the process of institutionalization of mobile banking and identified actions for improvement related to it.